Deficit irrigation effects on flowering of loquat - Hueso J.J.; Cuevas J. (First international symposium on loquat, 2003)
The experiment was carried out during three consecutive years on trees of cultivar 'Algerie'. Three treatments have been selected: Control (receiving about 40 percent of Epan measured with a Class A pan placed in the orchard), Continuous Deficit Irrigation (with stress uniformly applied throughout the year and 20 percent saving of water) and Regulated Deficit Irrigation (with the same reduction in irrigation, but stress concentrated on postharvest, from May to August, when reduction reached 55 percent of the amount of water received by controls). Control trees formed heavier flowers than deficit irrigation treatments, however, so far flower dry weight had no impact neither on quantity nor on quality of the fruits harvested. After three years of treatments, deficit irrigation has proved to be a feasible and a more profitable strategy to produce loquat.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)